Exploring Students’ Preferences of the Differences between British & American English - Muid, Abdul; Setiawan, Iwan; Suhatmady, Bibit (Globish: An English-Indonesian Journal for English, Education, and Culture, 2024)
The differences between American and British English have drawn more attention in the continually changing field of English language instruction. This study aimed to investigate students' preferences regarding the distinctions between British and American English in terms of spelling and lexical usage. Conducted using a quantitative approach, the research involved administering a vocabulary test to 129 ninth-grade students in a private junior high school in Bontang. The findings indicated a prevalent inclination towards American English, with a majority of students showing a preference for American English spellings and terminologies over British English counterparts. Specifically, the data revealed that American English was mostly favored in 63.4% of the cases analyzed, highlighting the significant influence of American English on the linguistic choices of students. These results contribute to a better understanding of how language variations impact language preferences among students, shedding light on the dominance of American English in contemporary educational settings.